Maids and School Teachers: Low Skill Migration and High Skill Labor Supply - Tiago Freire (European Regional Science Association (ERSA), 2010)
Over the 40 years the pattern of migration has changed significantly with an increase in the share of female migrants, and especially low skill female migrants. These low skilled women migrants often work in the domestic service sector, a close substitute for household work. This paper analyzes how low skill rural-urban migration in Brazil from 1986 to 2000 lead to an increase in the labor supply of high skill women living in urban areas. In our model we show how large inflows of low skill women migrants decrease the relative price of domestic services. The largest beneficiaries of this trend are high skill women, who respond to the decrease in the cost of domestic services by joining the labor force and working more hours. We use Census data from Brazil from 1991 and 2000 to test this hypothesis. Using weather shocks in rural areas, and historical patterns of migrations, we are able to build an exogenous migration shock by skill to cities. Using this as an instrument for the price of domestic services and local wages we find that a 10% decrease in the wage of domestic workers increases the labor participation of high skill women by 3%.
Keywords: J16; O15; O18; 330; Gender; Labor Supply; Migration; Rural Urban Migration; Skill Complementary